1 Timothy 4:1–5 as a neglected eschatological passage - Jacob J. Scholtz (In die Skriflig)
In 1 Timothy 4:1, the Spirit explicitly states that in later times some will devote themselves to the teachings of demons. While acknowledging the future implications of these doctrines, most commentators focus on their historical origins. To demonstrate that 1 Timothy 4:1–5 is an overlooked eschatological passage, this article examined the expression ‘later times’ (1 Tm 4:1), reconsidered the content of these demonic teachings (1 Tm 4:3a), and linked the passage (1 Tm 4:3b–5) to the Noahic covenant – and subsequently to end-time texts. It is argued that 1 Timothy 4:1–5 should be recognised as an eschatological passage that has often been neglected. The ‘later times’ (1 Tm 4:1) of the church age could serve as the backdrop for prophecies destined for fulfilment during the Tribulation Period.